Energy flow behavior and emission reduction of a turbo-charging and EGR non-road diesel engine equipped with DOC and DPF under NRTC (non-road transient cycle). (1st December 2021) - Hu, Songyu; Deng, Banglin; Wu, Di; Hou, Kaihong
Highlights: Energy balance and emissions of a non-road diesel engine were measured under Non-road Transient Cycle. A new concept "thermal delay effect" is proposed to explain the cooling loss. PN decreases to 4.30E + 09 #/kW·h by diesel particulate filter with efficiency of 99.99%. CO and HC are reduced to zero and NOx by 24.3% with diesel oxidation catalyst. Engine load plays the dominant role on non-road diesel engine emissions. Abstract: In the current study, the interaction between energy flow and aftertreatment is investigated by experiment to explore the energy distribution pattern changed by aftertreatment and the reversed impact on emission reduction. The temperature distribution, THC, CO/CO2, NOx and PN (particle number) emissions were measured in a non-road diesel engine with and without aftertreatment, DOC (diesel oxidation catalyst) and DPF (diesel particulate filter), under NRTC (non-road transient cycle) driving. With aftertreatment, the cooling loss is the main source for thermal efficiency reduction, a new concept "thermal delay effect" is proposed to explain this phenomenon. For emissions, overall CO and HC are almost reduced to zero through DOC, although CH4 conversion efficiency is only about 30%; NOx conversion efficiency is ~ 24.3%; and PN filtration efficiency is 99.99% through DPF. The engine meets the China national emission regulation even without aftertreatment except for PN, but PN decreases by five orders of magnitude through DPF. Finally, the emissions histories were analyzed in detail. The influencing factors were discussed thoroughly for original scenario. The exhaust temperature coupling with properties of catalytic converter were employed to analyze the aftertreatment's performance and its impact patterns on pollutants. Under operation pattern of back pressure compensation, the average exhaust temperature (300 °C) under aftertreatment scenario increased by 6% relative to without aftertreatment, while during most time it did not exceed 350 °C at which the NOx conversion began to drop. Thus this operation made a good trade-off among reductions of various pollutants. Therefore, the energy distribution analysis must be from the view point of integration between engine body and whole exhaust system to be sure of clarification about aftertreatment's behaviors.